Ответы и объяснения

2013-09-12T18:08:36+00:00
 
         3х-1           5х-2
2х+ --------------  -  -------------  -2   =0 /*6  
            2                 3    

12х+3*(3х-1)-2*(5х-2)-12=0
12х+9х-3-10х+4-12=0
12х+9х-10х=0+3-4+12
11х=11
х=11:11
х=1


26х-51       2*(1-3х)                  20х-(10-3х)   
-----------  -  ------------------  = х-   ----------------------------    

     52              13                             156

26х-51             2-6х                            17х-10   
---------------   -   -------------------    = х -   --------------------------------     /*156    
    52                   13                                      156 

3*(26х-51) - 12*(2-6х)=х-17х-10
78х-153-24+72х= -16х-10
78х+72х+16х= -10+153+24
166х=167
х=167:166
х=1 1/166